Combined experimental and computational investigation of the absorption spectra of E- and Z-cinnamic acids in solution: the peculiarity of Z-cinnamics - Salum, Maria Laura (2015)
Cinnamic acids are present in all kinds of plant tissues and hence in herbs and derived medicines, cosmetics and foods. The interest in their role in plants and their therapeutic applications has grown exponentially. Because of their molecular structure they can exist in E- and Z-forms, which are both found in plants. However, since only the E-forms are commercially available, very few in vitro and in vivo studies of the Z-form have been reported. In this work the physico-chemical properties of Z-cinnamic acids in solution have been examined by means of UV-absorption spectroscopy and high-level quantum mechanical computations. For each isomer similar absorption spectra were obtained in methanol and acetonitrile. However, distinct trends were found for Z- and E forms of cinnamic acids in water, where a higher hypsochromic shift of the Z-isomer relative to the E-form was observed. In general the wavelength of maximal absorption of the Z-form is dramatically blue shifted (−30 to −40 nm) to λ < 280 nm, while a slightly blue shift of the absorption maxima for the corresponding E-form (+3 to −4 nm) was observed. This difference is associated with the non-planar, largely distorted, Z-structure and to the almost complete flat structure of the E-form. The results provide a basis for the study of functional and biotechnological roles of cinnamic acids and for the analysis of samples containing mixture of both geometric isomers.